Variación en el patrón de crecimiento en altura de cuatro especies de Pinus en edades tempranas - Salazar García, Jesús Gustavo; Vargas Hernández, J. Jesús; Jasso Mata, Jesús; Molina Galán, José D.; Ramírez Herrera, Carlos; López Upton, Javier (Instituto de Ecología, A.C., 2016)
In order to determine the level of inter and intraspecific variation in height growth rate and number of growth cycles, an 18months old experimental plantation established at Patoltecoya, Puebla was evaluated during a 12-month period. The plantation includes a total of 30 provenances of four Pinus species (10 of P. greggii Engelm., 11 of P. patula Schl. et Cham., 4 of P. tecunumanii (Schw.) Eguiluz et Perry and 5 of P. maximinoi H. E. Moore), in a split-plot random block experimental design on two adjacent sites. Both site and site*genotype interaction had no significant effect on growth variables, but species and provenances within species showed a significant variation (p≤ 0.01) in all variables. Variation among species was 2 to 6 times higher than within species, so there is a greater selection potential at the species level for all variables measured. Pinus maximinoi and P. tecunumanii showed the highest growth rate (2.50 and 2.44 m year-1 respectively) while P. patula presented the lowest growth rate (1.92 m year-1). Height growth was negatively correlated (r = -0.98) with the number of growth cycles in P. tecunumanii and positively correlated (r = 0.75) in P. patula, but no significant correlation was found between these traits in P. greggii and P. maximinoi. In addition, each species showed a particular geographic variation pattern in these growth traits.